RANCANG-BANGUN APLIKASI SISTEM DISKUSI PEMBELAJARAN ON-LINE PADA PERGURUAN TINGGI - Aris Martono; Padeli Padeli; Rosalina Miliartha (CCIT Journal, 2016)
The development of information technology is growing rapidly as one of them used to interacting with other people. Information technology can connect us with others regardless of time and place. This is possible because of the existence of a container that community (forums) discussions on-line learning. However, in Higher Education of Raharja the development of discussion for learning is less developed for regular class or a class that is not a superclass or i-learning class because the manual is face to face or face to face for the discussion of learning in Higher Education of Raharja. Therefore, it can be made a formal community for container or the learning process in order to facilitate the discussion of faculty and students in the learning process outside of lecture hours that can be accessed anytime and anywhere and can provide accurate information so that the information obtained by the faculty and students to be more relevant. Discussion of web-based learning system is designed with a user friendly system so that is easy to access and understand, facilitate communication between faculty and students, and also facilitates getting materials lecture material, as well as assist in the distribution and collection of duties and tasks quickly lecturers also can manage the values that will given to students. The methodology used is a structured analysis and development ranging from analyzing the system that runs through UML, perform elicitation, and describes the proposed system through UML. The final results are achieved from this research is the creation of a learning system that can be accessed anywhere, anytime, and always follow the lecture material information or update